Representações do mirante do Morro Santa Teresinha no Diário do Nordeste: o jornal como instrumento de produção de territorialidades - Amaral, João Flávio Menezes (2019)
Between the 1980s and 1990s, two territories occupied the same geographic space: the Santa Terezinha Housing Complex, created to house families of fishermen displaced from the shore by the elites, and the Mirante, a natural observatory transformed in a touristic area and place for gastronomic and nightlife consumption of the middle and upper classes. This research seeks to understand how the local press was operationalized in the production and maintenance of these segregated territorialities that overlapped on the land of the Morro Santa Terezinha, in a coastal region of Fortaleza known as Mucuripe. Understanding that journalism is an ideological practice that represents the daily life of fragmented and segregated cities in an interdiscursive web, we analyse the content of a local newspaper and observe how the different representations that constituted and derived from journalistic discourse defined the Mirante as a territory in its own right, symbolically de-territorializing the original community, attributing distinctive meanings to it through the objectification of symbolic capital and adapting it to the consumption practices of the middle and upper classes. We identified how the production of identity and the association of symbols, the emphasis on difference and the negation of the surroundings were the main semantic strategies used in these processes. Through a methodological design that draws from procedures of Bardin’s (1977) Content Analysis and Fairclough’s (2001) Critical Discourse Analysis, we analyse 146 texts published in the newspaper Diário do Nordeste between 1983 and 2000, relating them to the work of historical contextualization of the Mirante, produced from collections of primary and secondary sources, as well as nine interviews with residents of the region, former consumers of the Mirante gentrified area and public officials.